Properties of Bovine Collagen as Influenced by High-Pressure Processing - Houška, Milan; Landfeld, Aleš; Novotná, Pavla; Strohalm, Jan; Šupová, Monika; Suchý, Tomáš; Chlup, Hynek; Skočilas, Jan; Štípek, Jan; Žaloudková, Margit; Šulc, Miloslav (Polymers, 2023)
The physical properties and structure of collagen treated with high-pressure technologies have not yet been investigated in detail. The main goal of this work was to determine whether this modern gentle technology significantly changes the properties of collagen. High pressure in the range of 0-400 MPa was used, and the rheological, mechanical, thermal, and structural properties of collagen were measured. The rheological properties measured in the area of linear viscoelasticity do not statistically significantly change due to the influence of pressure or the duration of pressure exposure. In addition, the mechanical properties measured by compression between two plates are not statistically significantly influenced by pressure value or pressure hold time. The thermal properties Ton and ∆H measured by differential calorimetry depend on pressure value and pressure hold time. Results from amino acids and FTIR analyses show that exposure of collagenous gels to high pressure (400 MPa), regardless of applied time (5 and 10 min), caused only minor changes in the primary and secondary structure and preserved collagenous polymeric integrity. SEM analysis did not show changes in collagen fibril ordering orientation over longer distances after applying 400 MPa of pressure for 10 min.